RANCANG BANGUN APLIKASI PEMINJAMAN DAN PENGEMBALIAN PERANGKAT TEKNOLOGI INFORMASI - Riza Syahrial; Jelman Nasri; Ramadhan Firdaus (JRIS : Jurnal Rekayasa Informasi Swadharma, 2022)
PT. Dayalima Abisatya, which is engaged in HR Consulting, still does not have a capable system to support business needs, one of which is in terms of lending information technology equipment for its business.Problems faced by lending are still carried out in various ways, such as by telephone, email, and even private messages to managers of information technology devices. Loan data storage is still in Microsoft Excel. There is a double record of borrowing due to data that is not real time. Loan reports in excel files often do not match. The purpose of this research is to design a system of borrowing and returning a web-based technology device. The results achieved are quite satisfactory and can run well according to the design